The deep femoral artery as a inflow source for distal reconstruction - Rusyn, V. I.; Korsak, V. V.; Rusyn, V. V.; Horlenco, F. V.; Dobosh, V. M. (Modern medical technology, 2019)
Purpose of the study. To improve the treatment outcomes of patients with occlusion-stenotic lesions of the femoral-popliteal-tibial segment, long-term results of the profundafemorispopliteal autologous vein bypass surgery have been studied. Material and methods. In the surgical clinic of A. Novak Regional Clinical Hospital during the last 10 years has been performed 300 isolated profundoplasty at chronic limb ischemia. In 16 patients with deep femoral popliteal autologous vein bypass, a distal segment of arteria profunda femoris was used as the «tidal» artery, which varied from 0,51 to 0,63 in diameter (0,58 cm in average). Results. In the immediate and long-term follow-up period, no thrombosis of profunda femoris popliteal autologous vein shunt was observed in 5 years. The ankle-brachial pressure index after surgery increases almost twice and approaches 0,9 on posterior tabial artery. The mean profunda popliteal collateral index score decreased to 0,301 ± 0,099 in all patients after surgery. Ifwecomparethequalityoflifeafterprofunda femoris popliteal autologous vein reconstruction, it should be noted that the quality of life in our patients before the operation was 21,8 ± 4,9 points, after the operation − 45,6 ± 4,9 points. Conclusion. Profundafemorispopliteal autologous vein bypass by a length of up to 15 cm provides blood supply to the limb with stenoticocclusive lesions of the femoral-popliteal-tibial segment, with the passage of at least one artery of the leg and the arteries of the pedis.